ENINGKATAN AKTIVITAS BELAJAR PESERTA DIDIK TENTANG SPEKTROFOTOMETRI MENGGUNAKAN METODE DRILL DI SMK-SMTI PONTIANAK - Wiwik Dwi Haryanti (Jurnal Pembelajaran Prospektif, 2022)
The increasing of learning activities in Natural Science By Using Drill Method In Grade XI APL students of Vocational High School Pontianak. The aim of this research is to improve Spectrophotometric learning activities. Research method is descriptive method. This research will be done in two cycle by the result is there is an increase of the cycle I to the cycle II as follows: forplanning learning ability assessment teachers experienced an increase in the amount of 0.2; for teaching ability assessment teachers, the increase the value of 0.06; the students learning activities to be an increase in the following physical activity there is an increase of 5.55 percent, mentalactivities there is an increase of 16.66 percent, and for such emotional there is an increase of 7.41 percent; and for the value students' achievement there is an increase value of average of 5.12. Conclusion from this class action research is using the methods drill in teaching Spectrophotometric can increase the students learning activities in grade Grade XI APL students of Vocational High School Pontianak.